The frequency and prognostic significance of ABO/Rh blood groups in male breast cancer patients: A multicenter study. Issue 35 (2nd September 2022) - Dogan, Izzet; Ayhan, Murat; Gurbuz, Mustafa; Kucukarda, Ahmet; Aydin, Esra; Urun, Yuksel; Cicin, Irfan; Saip, Pinar
Abstract : The study evaluated the distributions and prognostic significance of ABO and rhesus (D) groups in male breast cancer (MBC) patients. The data of 137 patients were retrospectively reviewed. Clinical, histopathological data and ABO/Rh blood groups of the patients were recorded. The ABO/Rh blood group distributions were compared to the healthy men control group (n = 120, 160) by the chi-square test. Overall distributions of ABO blood groups were different between the patients (17.5% AB, 38% A, 19% B, and 25.5% O) and control group (7.88% AB, 42.06% A, 15.22% B, and 34.84% O) ( P < .001). There were significant differences between the patients and control group with respect to AB vs non-AB blood group distributions ( P < .001, odds ratio: 2.43, 95% CI) and O vs non-O blood group distributions ( P = .016, odds ratio: 0.62, 95% CI). However, A vs non-A and B vs non-B blood group distributions were not significantly different. The distribution of the Rh factor was similar between patients and the control group ( P = .93). In univariate analysis, ABO/Rh blood groups were not a prognostic factor on OS ( P = .29). The frequency of the AB blood group in MBC patients is increased than in the healthy control group. AB blood group may be a risk factor for MBC, whereas O blood group may be a protective factor.